Automated Fluid Management for Treatment of Rhabdomyolysis - Christian M. Beilstein; John R. Prowle; Christopher J. Kirwan (International Journal of Nephrology)
Purpose. Fluid therapy aimed at increasing urine output is a commonly employed strategy to prevent acute kidney injury (AKI) in critically ill patients with rhabdomyolysis. Automated fluid management has the potential to optimise urine output while avoiding fluid accumulation in rhabdomyolysis patients. Methods. In a single centre clinical service evaluation we compared a convenience sample of critically ill adults with rhabdomyolysis treated with automated fluid management using the RenalGuard® device to patients managed with manual fluid adjustment following our standard rhabdomyolysis protocol. Primary outcome was number of hours with urine output >2 mL/kg during first 48 h of therapy. Results. Eight patients treated with RenalGuard were compared to 28 patients treated with manual fluid management. Number of hours of target urine output was greater in the RenalGuard versus the Standard group (176/312 (56.4%) versus 534/1305 (40.9%); p<0.01). Urine output was significantly higher in the first 24 h in the RenalGuard group (median (IQR) 4033 mL (3682–7363) versus 2913 mL (2263–4188 mL); p<0.01). Fluid balance, electrolyte, diuretics, and bicarbonate use were comparable between groups. Conclusions. Automated fluid management resulted in a higher urine output more quickly in the treatment of rhabdomyolysis. Further research is needed to analyse the effect of diuresis-matched hydration for the prevention of AKI in rhabdomyolysis.